Minimally Invasive Management of Retinal Detachment: Insights from a Pneumatic Retinopexy Case Report - Pramesti, Karina Ayu; Prakosa, Ady Dwi; Sasono, Wimbo; Firmansjah, Muhammad; Widjaja, Sauli Ari; Yustiarini, Ima (International Journal of Retina, 2025)
Introduction: Rhegmatogenous Retinal Detachment (RRD) caused by a tear in the retina, causes fluid accumulation and separation of neurosensory retina from retinal pigment epithelium which can lead to blindness. The goal for treatment is to reduce vitreoretinal tension and fix retinal tears and holes. The case report discusses about management in uncomplicated RRD. Case Report: Patient came with blurry vision on his right eye (RE) since two weeks ago. Four days before, He was seeing black curtain on lower left direction while working, but it did not get any wider. No complaints on his left eye. Patient has hypertension only known recently. No history of trauma, spectacles. His occupation was labourer. General examination within normal limits. Visual acuity (VA) RE 6/24. Anterior segment within normal limits. Posterior segment, detachment at 9-2 o'clock, horse shoe tear at 11 o'clock and a small hole at 1 o'clock. Lattice degeneration at 8-12 o'clock, macula on. Patient then underwent pneumatic retinopexy. Intraocular pressure (IOP) 13mmHg. Discussion: Retinal detachment occurs when subretinal fluid accumulates between the neurosensory retina and the retinal pigment epithelium. This can happen in three ways, and the cause for our patient was a tear of retina, for that reason we diagnosed with RRD. Prognosis for patients with RRD depends on the condition off the macula, and the symptom onset. Conclusion: Optimization of retinal detachment detection and the success of rapid-onset retinopexy still need improvement. Proliferative Vitreoretinopathy (PVR) remains a common cause of failure, necessitating new strategies for its management. However, the choice of technique is still influenced by the considerations and experience of each vitreoretinal surgeon.